SOME ISSUES OF GUILTINESS IN AFFECTIVE MURDER - Mukhadze, Giorgi (European Scientific Journal, ESJ, 2013)
﻿﻿The given article deals with the interests towards fit of passion of murder in the Science of Criminal Law of Georgia which already exists for a long time. It is stipulated by two causes: firstly, by permanent necessity towards investigation – judiciary practice which demands precise criteria of qualification of the act; secondly, by essential changes of criminal law doctrine in Georgia which caused working out of the new approach towards the problem of guilt. Consequently, Georgian scientists had to review a whole range of conceptions which did not answer demands of the present day. It is clear that due to complexity of the issue, it is hard to discuss approach of all conceptions in one article. We shall light briefly peculiarities of approach of Georgian scientists towards some conceptions. We should single out only so called argumentations of estimation for criminal and subject conceptions of psychological crime of guilt.